Pengaruh Anger Management Terhadap Pengontrolan Rasa Marah Pada Pasien Dengan Resiko Perilaku Kekerasan Di Wilayah Kerja Puskesmas Limboto - Hermawati Harun; Hamna Vonny Lasanudin; Inne Ariane Gobel; Nur Uyuun I Biahimo (Sekolah Tinggi Ilmu Kesehatan Stella Maris Makassar, 2026)
Emotional instability in schizophrenia sufferers often triggers the risk of violent behavior (VBD). The phenomenon at Limboto Community Health Center indicates that VBD occurs due to poor anger management in patients, which puts them at risk of harm to themselves and those around them. The purpose of this study was to determine the effect of anger management on anger control in RPK patients in the Limboto Community Health Center work area. This research method was a quantitative quasi-experiment with a one-group pretest-posttest design approach. The sample consisted of 38 schizophrenia respondents with RPK who were taken using the Slovin formula through a purposive sampling technique. The data collection instrument used the Clinical Anger Scale (CAS) questionnaire which was analyzed using a parametric paired t-test. The results of the study, where before the intervention, the average score of respondents' anger control was 51.74 (moderate category). After being given anger management therapy, the average score of anger control decreased significantly to 31.50 (high category) with a decrease difference of 20.23. The paired t-test results showed a p-value of 0.000 (p < 0.05). The conclusion is that there is a significant effect of anger management intervention on improving anger control skills in patients with RPK at the Limboto Community Health Center. Community health center nurses can implement this intervention as part of independent or group nursing actions to consistently train patients' self-control skills, so that it is effective in minimizing aggressive behavior and reducing relapse rates.